Religious Adaptation in Times of Crisis: Muhammadiyah Tarjih Council’s Fatwas on Islamic Practices During the COVID-19 Pandemic - Ahmadi, Ahmadi; Mahrudin, Mahrudin; Alifuddin, Muhammad; Ilham, Muhammad (Institut Agama Islam Negeri Kendari, 2025)
The study aim to examine in a way in depth fundamental ideas of Muhammadiyah face at a time do mitigation disaster covid19 pandemic through religious fatwa. The data in this study were obtained through studies containing documents related to organ policies about mitigation covid19 disaster. This data is important in terms of the interpretive paradigm, thus requiring researchers to understand the reasons of the actors in issuing religious policies and fatwas as mitigation measures. Data analysis continues continuously, with reference to the combined Miles and Huberman mechanism with method phenomenology hermeneutics from von Eckartsberg. The findings of the study are that Muhammadiyah looked at the effort subtraction risk. The COVID-19 disaster is a religious social obligation. So, besides deploying resources and infrastructure health, Muhammadiyah also educates the public through a fatwa about the ability to “change” patterns of religious rituals that are carried out during the pandemic. Tarjih Muhammadiyah fatwa was issued to embody the implementation of health protocols in order to avoid bigger harm, all at once giving basic arguments and beliefs to the public that changing the pattern of ritual action during the Covid-19 pandemic is not a religious deviation. Ritual action patterns that were previously carried out en masse in mosques and the field can be shifted to private spaces. Likewise, with the sacrificial slaughter ritual, it is more advisable to prioritise infaq based on economic empowerment, especially for subjects affected by the socio-economic impact of the pandemic situation. Change pattern religious ritual habits issued by Muhammadiyah as an action to mitigate disaster based on principles of maqasid Sharia in the framework of looking after the continuity of life (hifdz an-nafs). Conclusion about hidz The nafs underlying the Fatwa of Tarjih Muhammadiyah was obtained through reasoning by Burhani, Bayani and Irfani.